Black Tea: A Comprehensive Review - Yushinta Aristina Sanjaya; Ardita Putri Apriliani; Mufida Naima Rohmah (Nusantara Science and Technology Proceedings, 2023)
Tea is one of the most popular refreshing drinks due to its strong and delicious flavor, it is also known to have many health benefits. Tea comes from the tops (shoots) of the leaves of the Camellia sinensis plant which are processed and then dried. Black tea is the most widely produced tea in Indonesia, which is about 78% of the total tea production. Black tea can be divided into two categories based on the process, namely orthodox and CTC black tea, which are known to contain many chemical compounds that are good for the body. The content of chemical compounds in tea is generally contained in its leaves which are classified into four major groups, namely phenol groups, non-phenol groups, aromatic compound groups, and enzymes. The content of chemical compounds present in tea will form the physical characteristics of tea, namely appearance, liquor, and infused leaf. Many research found that black tea could reducing the accumulation of dental plaque, preventing obesity, preventing cardiovascular disease, as an antibacterial and anticancer, and preventing osteoporosis. The compound epigallocatechin gallate which is the main component in tea has been shown to have insulin-potentiating activity. In addition, theaflavin compound in tea is also known to inhibit the entry of HIV-1 in the body.